Extraction of Pr(III), Nd(III), and Dy(III) from HTFSA Aqueous Solution by TODGA/Phosphonium-Based Ionic Liquids. Issue 2 (23rd February 2016) - Murakami, Sena; Matsumiya, Masahiko; Yamada, Takahiro; Tsunashima, Katsuhiko
ABSTRACT: The extraction behavior of rare earth (RE) elements using N, N, N ′, N ′-tetraoctyl diglycolamide (TODGA) in an ionic liquid (IL) system was investigated by slope analyses. Metallic salts of Pr(III), Nd(III), and Dy(III) with bis(trifluoromethylsulfonyl)amide (TFSA) were synthesized and studied for their extraction mechanism. The selected concentration of TODGA was diluted with triethylpentylphosphonium bis(trifluoromethylsulfonyl)amide ([P2225 ][TFSA]) to prepare an extracting phase for the slope analyses. The stoichiometry of RE(III) was determined in order to estimate the extracted species. Furthermore, the complexation state of the extracted species was evaluated by spectroscopic analyses, including Fourier-transform infrared (FT-IR) spectroscopy, Raman spectroscopy, and ultraviolet–visible (UV–Vis) spectroscopy. The FT-IR and Raman spectra were estimated using density functional theory (DFT) calculations. Thorough analysis of the FT-IR spectrum was carried out in order to assign the TODGA group that mainly coordinated the metal ion. The solvation of the [TFSA] − anion in the coordination sphere of [Nd(TODGA)(2–3) ] 3+ was investigated by Raman spectroscopic analysis. The coordination ability of TODGA was investigated from the peak shift of the hypersensitive transition ( 4 I9/2 → 2 G7/2 ) in UV–Vis spectroscopic measurements. From electrochemical analysis, the extracted [Nd(TODGA)3 ] 3+ complex in [P2225 ][TFSA] was found to be reduced as per the following reaction: [Nd(TODGA)3 ] 3+ + 3e − → Nd(0) + 3[TODGA] at −3.0 V, and the diffusion coefficient of [Nd(TODGA)3 ] 3+ was calculated to be 1.6 × 10 −11 m 2 s −1 at 373 K. The direct electrodeposition of the extracted [Nd(TODGA)3 ] 3+ in [P2225 ][TFSA] at 373 K allowed us to conclude that the middle layer of Nd electrodeposits was the metallic state, while a part of the top surface was the oxidation state by XPS analysis.